Community Knowledge and Behavior in the Utilization of Medicinal Plants in Cikoneng Village Bandung District - Rahimah, Santun Bhekti; Kharisma, Yuktiana; Nurhayati, Eka; Yuniarti, Yuniarti; Santoso, Shenny Dianathasari; Faridza, Muhammad (Universitas Islam Bandung, 2019)
The industry of the traditional medicinal made from medicinal plants was currently growing. Effortless cultivation and utilization of medicinal plants were an important step to preserve the traditional medicine of Indonesia. Cikoneng village had abundant natural potential and is an assisted village of the researchers' institution located at the foot of Manglayang mountain Bandung district. Therefore, the researchers implemented the intervention program to educate and socialize the use of medicinal plants to the community of Cikoneng village. After the intervention program, the assessment of the level of knowledge and perceptions of people in the behavior of treatment by medicinal plants utilized was carried out. This study aims to assess the increase in knowledge and perceptions of people in the behavior of cultivation and treatment by using medicinal plants in Cikoneng village. The study used an intervention program and questionnaire with 35 respondents conducted on 22 August–23 September 2016. The results showed that after the intervention program, the level of knowledge of the Cikoneng village community regarding medicinal plants was right. The entire people of Cikoneng village is willing to take advantage of medicinal plants in maintaining family health and will begin to cultivate them in the smallest scope (family). In conclusion, there is an increase in people's knowledge and perception of the behavior of cultivation and treatment by utilizing medicinal plants in Cikoneng village. PENGETAHUAN DAN PERILAKU MASYARAKAT DALAM PEMANFAATAN TANAMAN OBAT DI KAMPUNG CIKONENG KABUPATEN BANDUNGIndustri obat tradisional berbahan baku tanaman obat saat ini semakin berkembang. Upaya budidaya dan pemanfaatan tanaman obat yang optimal merupakan langkah penting untuk menjaga kelestarian obat tradisional Indonesia. Kampung Cikoneng mempunyai potensi alam yang melimpah dan merupakan desa binaan institusi peneliti yang terletak di kaki Gunung Manglayang Kabupaten Bandung. Oleh karena itu, peneliti melaksanakan program intervensi untuk mengedukasi dan menyosialisasikan pemanfaatan tanaman obat kepada masyarakat Kampung Cikoneng. Pada akhir program intervensi, dilakukan penilaian tingkat pengetahuan dan persepsi masyarakat tentang perilaku pengobatan dengan tanaman obat. Penelitian ini bertujuan menilai peningkatan pengetahuan dan persepsi masyarakat tentang perilaku budidaya dan pengobatan dengan memanfaatkan tanaman obat di Kampung Cikoneng. Penelitian menggunakan program intervensi dan kuesioner dengan jumlah responden 35 orang yang dilaksanakan pada 22 Agustus–23 September 2016. Hasil memperlihatkan bahwa setelah program intervensi, tingkat pengetahuan masyarakat Kampung Cikoneng mengenai tanaman obat adalah baik. Seluruh masyarakat Kampung Cikoneng bersedia memanfaatkan tanaman obat dalam menjaga kesehatan keluarga dan akan mulai membudidayakannya dalam lingkup yang paling kecil (keluarga). Simpulan, terdapat peningkatan pengetahuan dan persepsi masyarakat tentang perilaku pengobatan dengan memanfaatkan tanaman obat di Kampung Cikoneng.